Microeconomic dynamics of FDI and local innovation: A firm level estimation of Chilean firms - Ignacio Silva Neira; Carlos Rodríguez González; Jennifer Pédussel Wu (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2025)
Globalization has significantly influenced economic policy in Latin America. After the debt crisis of the 1980s, capital controls were removed leading to a substantial increase in Foreign Direct Investment (FDI) to the region. Chile, in particular, has extensively promoted free international integration, with the import of technology through FDI playing a major role in its economic development. During the 1990s, Chile experienced a period of rapid GDP growth, increased exports, and higher productivity. However, its productive dynamism has since stalled, trapping the country in an income plateau. Insights from evolutionary economics provide a framework for understanding this phenomenon, where neoclassical theory falls short. This study seeks to provide empirical evidence on whether FDI has promoted or hindered the innovative performance of domestic firms in Chile. Using firm-level data, the research employs the well-known CDM model to address selection bias in innovation efforts. The econometric analysis measures the impact of foreign competition on local innovation, specifically examining how foreign ownership and competition within economic sectors influence innovation outputs in local firms. The findings indicate that firms facing higher levels of foreign competition are less likely to implement new processes or products. These results offer valuable policy implications, highlighting the nuanced effects of FDI on host economies. The impact of FDI varies depending on the type of investment, the economic sector, and the technology introduced. Consequently, strategies aimed at leveraging FDI for economic catch-up must account for these variances and focus on fostering local innovation and technological advancement.
Keywords: F21; O33; L25; O54; D22; 330; Foreign Direct Investment; CDM Model; Innovation; Technology transfer